Hypervariable Domain of Eastern Equine Encephalitis Virus nsP3 Redundantly Utilizes Multiple Cellular Proteins for Replication Complex Assembly - Frolov, Ilya (J Virol, 2017)
Eastern equine encephalitis virus (EEEV) is a representative member of the New World alphaviruses. It is pathogenic for a variety of vertebrate hosts, in which EEEV induces a highly debilitating disease, and the outcomes are frequently lethal. Despite a significant public health threat, the molecular mechanism of EEEV replication and interaction with hosts is poorly understood. Our previously published data and those of other teams have demonstrated that hypervariable domains (HVDs) of the alphavirus nsP3 protein interact with virus-specific host factors and play critical roles in assembly of viral replication complexes (vRCs). The most abundantly represented HVD-binding proteins are the FXR and G3BP family members. FXR proteins drive the assembly of vRCs of Venezuelan equine encephalitis virus (VEEV), and G3BPs were shown to function in vRC assembly in the replication of chikungunya and Sindbis viruses. Our new study demonstrates that EEEV exhibits a unique level of redundancy in the use of host factors in RNA replication. EEEV efficiently utilizes both the VEEV-specific FXR protein family and the Old World alphavirus-specific G3BP protein family. A lack of interaction with either FXRs or G3BPs does not affect vRC formation; however, removal of EEEV's ability to interact with both protein families has a deleterious effect on virus growth. Other identified EEEV nsP3 HVD-interacting host proteins are also capable of supporting EEEV replication, albeit with a dramatically lower efficiency. The ability to use a wide range of host factors with redundant functions in vRC assembly and function provides a plausible explanation for the efficient replication of EEEV and may contribute to its highly pathogenic phenotype. IMPORTANCE Eastern equine encephalitis virus (EEEV) is one of the most pathogenic New World alphaviruses. Despite the continuous public health threat, to date, the molecular mechanisms of its very efficient replication and high virulence are not sufficiently understood. The results of this new study demonstrate that North American EEEV exhibits a high level of redundancy in using host factors in replication complex assembly and virus replication. The hypervariable domain of the EEEV nsP3 protein interacts with all of the members of the FXR and G3BP protein families, and only a lack of interaction with both protein families strongly affects virus replication rates. Other identified HVD-binding factors are also involved in EEEV replication, but their roles are not as critical as those of FXRs and G3BPs. The new data present a plausible explanation for the exceptionally high replication rates of EEEV and suggest a new means of its attenuation and new targets for screening of antiviral drugs.